GAMBARAN PENGETAHUAN IBU HAMIL DENGAN KEJADIAN BAYI BERAT LAHIR RENDAH DI RSUD TENRIAWARU KELAS B KABUPATEN BONE - Hasnidar (Jurnal Suara Kesehatan, 2015)
Birth weight is one of the indicators in a child's development until adulthood and describes the nutritional status obtained by the fetus during pregnancy. Low birth weight (LBW) babies are newborns weighing less than 2,500 grams. The purpose of this study was to describe the knowledge of pregnant women on the incidence of low birth weight babies. This research method uses descriptive design, data collection used is primary data by distributing questionnaires to respondents related to knowledge about low birth weight babies, causes and prevention of low birth weight babies. The population in this study were all pregnant women who performed ANC examinations at the Class B Tenriawaru Hospital, Bone Regency in 2014 and the sample in this study were 60 respondents and the sampling technique was using total sampling technique. From these data obtained several descriptions of the knowledge of pregnant women about the meaning of low birth weight babies have good knowledge (41.7%), sufficient (28.3%), less (30.0%). Knowledge of pregnant women about the causes of LBW, the knowledge good (28.3%), sufficient (43.4%), insufficient (28.3%). The knowledge of pregnant women about the prevention of LBW is that they are good (31.7%), sufficient (21.7%), less (46.6%). In this study, it is hoped that pregnant women will increase their knowledge about low birth weight babies and the causes and impacts of low birth weight babies, through print or TV or radio. As well as for health workers to further increase outreach activities about LBW through various ways that are well accepted by the community